Beiträge zur Insektenfauna der DDR: Diptera - Sciaridae. - Menzel, Frank; Mohrig, Werner; Groth, Ilselotte (Contributions to Entomology = Beiträge zur Entomologie, 1990)
At present the known Sciarid fauna of the GDR consists of 172 species belonging to 18 genera. 26 species are described as new. The male genitalia of the new species are figured, 4 new synonyms and 6 new combinations have been found. New data concerning the habitats and geographic distribution in the GDR and the Palaearctic region are given for all species. This study is mainly based on the material of the collection of W. Mohrig, which is deposited (including all types) in the Zoological Museums of the Ernst-Moritz-Arndt-University Greifswald (GDR). Nomenclatural Acts bulbostyla Mohrig & Menzel, 1990 (Bradysia), spec. n. castanea Mohrig & Menzel, 1990 (Bradysia), spec. n. edwardsi Freeman, 1983 (Bradysia), syn. n. of Bradysia polonica (Lengersdorf, 1929) flavohalterata Mohrig & Menzel, 1990 (Bradysia), spec. n. lembkei Mohrig & Menzel, 1990 (Bradysia), spec. n. lilienthalae Mohrig & Menzel, 1990 (Bradysia), spec. n. longicauda Mohrig & Menzel, 1990 (Bradysia), spec. n. longicubitalis (Lengersdorf, 1924) (Bradysia), comb. n. hitherto Cratyna longicubitalis pectinata Mohrig & Menzel, 1990 (Bradysia), spec. n. postrufescens Mohrig & Menzel, 1990 (Bradysia), spec. n. procera Mohrig & Menzel, 1990 (Bradysia), spec. n. spinostyla Mohrig & Menzel, 1990 (Bradysia), spec. n. subgiraudi Mohrig & Menzel, 1990 (Bradysia), spec. n. subscabricornis Mohrig & Menzel, 1990 (Bradysia), spec. n. tenuicauda Mohrig & Menzel, 1990 (Bradysia), spec. n. arboris Fritz, 1983 (Corynoptera), syn. n. of Corynoptera saccata Tuomikoski, 1960 curviforceps (Bukowski & Lengersdorf, 1936) (Corynoptera), comb. n. hitherto Neosciara curviforceps densiseta Mohrig & Menzel, 1990 (Corynoptera), spec. n. dentata (Bukowski & Lengersdorf, 1936) (Corynoptera), comb. n. hitherto Neosciara dentata dentiforceps (Bukowski & Lengersdorf, 1936) (Corynoptera), comb. n. hitherto Neosciara dentiforceps grothae Mohrig & Menzel, 1990 (Corynoptera), spec. n. nigrocauda Mohrig & Menzel, 1990 (Corynoptera), spec. n. subforcipata Mohrig & Menzel, 1990 (Corynoptera), spec. n. uniformis Mohrig & Menzel, 1990 (Corynoptera), spec. n. lutea (Meigen, 1804) (Ctenosciara), comb. n. hitherto Sciara lutea leucocera Mohrig & Menzel, 1990 (Lycoriella (Hemineurina)), spec. n. preavenosa Mohrig & Menzel, 1990 (Lycoriella (Hemineurina)), spec. n. secundaria Mohrig & Menzel, 1990 (Lycoriella (Hemineurina)), spec. n. acutostylia Mohrig & Menzel, 1990 (Lycoriella (Lycoriella)), spec. n. micria Mohrig & Menzel, 1990 (Lycoriella (Lycoriella)), spec. n. perochaeta Mohrig & Menzel, 1990 (Lycoriella (Lycoriella)), spec. n. piniphila Lengersdorf, 1940 (Neosciara), syn. n. of Corynoptera spoeckeri (Lengersdorf, 1930) paraglobula (Rudzinski, 1988) (Plastosciara), comb. n. hitherto Cotynoptera paraglobula barbula Mohrig & Mamaev, 1985 (Scaptosciara), syn. n. of Scatopsciara multispina (Bukowski & Lengersdorf, 1936) denudata Mohrig & Menzel, 1990 (Scatopsciara), spec. n. melanoma Mohrig & Menzel, 1990 (Trichosia (Leptosciarella)), spec. n.